The temptations of tyranny in Central Asia - Lewis, David 1967- (Columbia University Press, 2008)
"The Temptations of Tyranny in Central Asia investigates why the U.S. alliance with Uzbekistan failed to produce reform and instead ended with the massacre of hundreds of civilians in Andijan. David Lewis provides the first detailed account of the 2005 revolution in Kyrgyzstan and examines the Islamic militant groups that are believed to be threatening stability in the Ferghana Basin. He also explores the political transition in Turkmenistan following the death of its eccentric former leader, Saparamurat Niyazov, and the bizarre dictatorship that threatens to turn the country into the next North Korea." "Lewis concludes with a look at the lessons that can be learned from the practice of Western policy in Central Asia, addressing the possibility of democratization in the Islamic world; the myths and realities of Islamist militancy; the role of authoritarian states in inciting radicalism and violence; the conflict between security relationships and rhetorical commitments to democracy and human rights within U.S. policy; and the competing interests of China, Russia, and American in the region."--Jacket